Pengaruh Motivasi Dan Tingkat Literasi Terhadap Minat Mahasiswa Untuk Memutuskan Berinvestasi Di Pasar Modal - Yuliantoro, Heri Ribut; Nurmalasari, Dini; Tinambunan, Theresia Elfina (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study looked at how students' motivation and literacy levels related to their interest in share investment. All Politeknik Caltex Riau Investment Gallery registered students enrolled in the Accounting Study Program served as the study's subjects; they were chosen from a sample. A total of 100 student data sets were examined based on sample selection. In order to evaluate the data and make conclusions, this research use multiple regression approaches along with conventional assumption testing and hypothesis testing through a data processing tool. The study's findings demonstrate that, among the 100 student data examined, motivation and reading proficiency had a major impact on students' levels of interest. The study's findings revealed that most pupils who were enthusiastic about.